Análise epidemiológica e bioeconômica da mastite bovina em rebanhos brasileiros - Camila Stefanie Fonseca de Oliveira (2015)
Mastitis is regarded to be one of the most common production diseases in cattle worldwide, one of the main causes of economic losses in dairy farms, hard to control. The diagnose of factors that affect livestock production has a major impact on the efficiency of dairy farming properties, they allow the implementation of more targeted control measures improving the sustainability of farms. However, there are few studies estimating the costs of diseases in developing countries, either the costs of mastitis in dairy cattle. In Brazil, the situation is even more complex due to the heterogeneity of dairy farms. Given this, this study aimed to characterize the risk factors of bovine mastitis, the factors that generate the costs of bovine mastitis and adapt stochastic mathematical modeling, to create a more accurate estimate of the costs of mastitis in Brazilian dairy herds.